O conceito de phrónesis na ética de Paul Ricoeur - Silva, Bruno Fleck da (2020)
The theme of practical wisdom in Paul Ricoeur's philosophy is constituted as a philosophical horizon that reflects intentional experiences in an ethical and hermeneutic scope, also directing itself to the practical field of moral judgment in a situation. The present research is intended to analyze the theoretical path that led Ricoeur to value this theme. Initially, from the triple phenomenological, hermeneutic and ethical link, the place of ethics in the philosophy of the French thinker is evidenced from the theme of ipseity: in a horizon of recognition, person and promise culminate in the action of the self from the plans of the ethical and moral perspective. These poles, that of ethics and morals, are examined from Ricoeur's petit éthique: that is, by their implication in the spheres of ipseity, otherness and justice, that is, of the self, the other and the community. It is from this path, through the ethical and moral approach of these three spheres, that the challenges of conscience in action and in terms of moral judgment in a situation are announced. Practical wisdom results from a conscience with and for others that responds to conflicts as a conviction and not as a response. The passage of the action of the self is from an ethical (teleological) horizon, it needs the sieve of the norm, that is, from another horizon, that of moral obligation (deontological), which implies the conflict, so well represented in the tradition by the theme of tragedy. In these cases of conflict, conscience and judgment find in practical wisdom the return to the essential sphere, of an ethics reinforced by morality that can effect justice as equity. Such an undertaking is designed as the experience of regional ethics and dialogue that leads to the conviction of the good for all according to prudential action (phrónesis). Uncertainty and urgency as characteristics of the tragic give practical wisdom a model of the preeminence of the just in terms of a practical philosophy. Selfhood on an ethical level and in the face of tragicity resorts to conviction exercising a practical wisdom that makes the self the self supported by virtue, respect and justice. The attestation of the self is, on the ethical level, the unfolding to the other in the fair reception that makes conviction the practical knowledge of an equitable ethics.